A Comparative Investigation of Kerf Width During CO2 and Fiber Laser Machining of SS 316L Material - Sargar, Tukaram; Gautam, Nitish Kumar; Jadhav, Aniket; Gaikwad, Mahendra U. (Recent Patents on Mechanical Engineering, 2025)
IntroductionThe unconventional thermal machining method of laser cutting is extensively used. Using this method, any material, essentially, having intricate geometries is machined accurately. The primary purpose of the current paper is to investigate how process factors affect kerf width for CO2 and fiber laser machining of the SS 316L method. This work mainly focuses on an experimental study of CO2 and fiber laser machining for SS 316L.MethodsChanging process variables, including gas pressure, laser power, and cutting speed, the cut characteristics are assessed using the measurement of kerf width. A bystronic laser machine is used for the experimentation.ResultsThe design of the experiment (DOE) technique is applied using the response surface methodology and Box Behnken design. In this, three factors and two levels are chosen, resulting in 17 trial runs. ANOVA is used to perform mathematical computations. This paper also covers the research on SS 316L laser machining and identifies the optimized parameter. The major finding of this research is that changing the laser power affects the kerf width. The CO2 and fiber laser processing results in optimum kerf width values of 0.5726 mm and 0.3950 mm, respectively.ConclusionThis study contributes to the understanding of laser machining of SS 316L and is a valuable resource for potential patent applications related to laser cutting technologies and optimized machining parameters.
Keywords: DOE